Pengembangan model pembelajaran instruksional design dengan model Addie mata pelajaran PAI pada materi mengulang-ulang hafalan Surah Al Ma’un dan al Fil secara klasikal, kelompok dan individu kelas V SDN Gedongan 2 Kota Mojokerto - Isya', Muhammad Andi (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Learning Design is the ordinance used to implement the learning process. The concept of learning design was first used in World War II and beyond. According to Jerrold E. Kemp, at that time psychologists introduced new theories about human learning process, including the importance of detailing the tasks to be learned and implemented, and the need for students to play an active role so they actually learn. The purpose of this research development are: 1) to describe instructional instructional model design with Addie model of Islamic Education subject on repetition materials of Surah Al Ma'un and al Fil in classical, group and individual class V SDN Gedongan 2 Kota Mojokerto according to Expert. 2) To describe instructional instructional model design with Addie model of Islamic Education subject on repetition of Surah Al Ma'un and al Fil in classical, group and individual class V SDN Gedongan 2 Kota Mojokerto according to peers 3) To describe learning model Instructional design with Addie model of Islamic Education subject on material repeating Surah Al Ma'un and Al Fil recitation classically, group and individual class V SDN Gedongan 2 Kota Mojokerto according to students. The selection and use of instructional instructional design model with Addie model correctly can streamline and streamline the implementation of learning. For that purpose the instructional instructional model design with Addie model is absolutely necessary. The product of instructional instructional model design with Addie model of Islamic Education subject on the material repeating Surah Al Ma'un and al Fil memorized classically, this group and individual has been perfected based on analysis of trial data. Based on the steps that have been implemented can be concluded as follows. 1). Instructional instruction model design with Addie model of Islamic Education subject on the material repeating the recitation of Surah Al Ma'un and al Fil in classical, group and individual class V SDN Gedongan 2 Kota Mojokerto according to Expert. Got score of 3.95 with enough category 2) instructional model design with model Addie subjects Islamic Religious Education on the material repetition of Surah Al Ma'un and al Fil in classical, group and individual class V SDN Gedongan 2 City Mojokerto according to peers Got a score of 3.9 with enough category.3) instructional instructional model design with Addie model of Islamic Education subjects on the material repetitively recitation Surah Al Ma'un and al Fil in classical, group and individual class V SDN Gedongan 2 Mojokerto according to the students Is 3.61, it is categorized Self by standard intersection of 0.30 points is sufficiently categorized